Anticipating the unexpected: between desire and alchemy - Silva, Cidália Maria Ferreira (2015)
This paper discusses the practice of the unknown in the realm of research. Why the unknown? Simply stated, it has the potency for actual change. Research tends to be bound to predetermined methods, the means of which knowledge is produced. Here the opposite is explored: how to research with a practice in which both method and knowledge are unknown? It considers two premises: (a) there is an attachment between method and the produced knowledge; (b) if you follow certain and predetermined methods you constrain the knowledge to ‘what you already know’ (past), limiting the possibilities of discovering the unknown. A good example is that important discoveries in science were made by chance or mistake. Here the explored practice contains a strong instability and uncertainty. The experience is unstable; the result is unpredictable and unexpected. In this realm, the predictable and the expected are not synonymous with anticipation. This implies that the challenge is not to anticipate the predictable but the opposite, overcoming the linearity of history and the simplistic views of deterministic cause-effect. The tools for anticipating the unexpected are desire, philia, potency, and alchemy. Desire is explored from the Gilles Deleuze perspective; it is by the means of the process of desire itself that things become actual, which is different from the common notion that considers the desire for something that is lacking, i.e., as an object. Philia, the Greek word for love, friendship, is looked at through the lens of Spinoza, Epicurus, and also Joseph Campbell’s maxim to ‘follow your bliss’. Potency, stimulated by Nietzsche, is the power to overcome what instability, that which causes the judgmental self-talk of wrongness. Developed at the School of Architecture of University of Minho, each tool is explored through innovative research projects that share a common ground: embracing uncertainty, moving forward with no predetermined plan, through which unexpected knowing is created about the everyday places we inhabit. Cedric Price’s (1996) ideas of “anticipating the unexpected” are also integrated into this discussion. Alchemy is the device for continuous transmutation of the ‘me into you,’ the ‘not-known into the known,’ which aims to make a responsible contribution “toward (...) effectively addressing the pressing challenges confronting humanity [places] of today.” Although generated in the field of architecture, this approach could be a catalyst for change in other fields of knowledge.